CO-RELATION BETWEEN FRACTURE FIXATION DEVICE AND CONVENTIONAL PHYSIOTHERAPY ON FUNCTIONAL MOBILITY OUTCOME IN POST-MENOPAUSAL WOMEN - Kotian, Nayan Sandeep; Shinde, Sandeep Babasaheb (International Journal of Psychosocial Rehabilitation, 2020)
In post-menopausal women, there is an increased risk of osteoporosis due to lower levels of estrogen hormone. The frequency of intertrochanteric fractures in these post-menopausal women is not uncommon. This study focuses on finding correlation between the fracture fixation device used for Intertrochanteric femur fracture and conventional physiotherapy on functional mobility outcome in the post-menopausal women. Methodology:In this observational study, 33 post-menopausal women undergone unilateral Intertrochanteric femur fracture fixation 6 months ago using Dynamic Hip Screw with plating were chosen. The subjects who were given conventional physiotherapy treatment in their post-operative phase were enrolled. An Assessment was performed using berg balance scale, gait parameters, Timed up and go test. Data was obtained and a correlation was established.Result: An overall quality of life was found to be better in the post-menopausal women between the age group of 55 and 75 years. There was an average decline of 35.44% in the berg balance scale score when compared to normal score. Gait parameters were found to be averagely better in the age group between 55 and 65 years while less than normal in the age group between 66 to 75 years. The TUG test scores showed that the post-menopausal women need assistance to perform asthey are at medium risk for falls. However, an improvement in muscle in muscle was established resulting in the functional mobility in the post-menopausal women. Conclusion: Thus, a correlation between fracture fixation device used for intertrochanteric fracture of femur and conventional physiotherapy on functional mobility outcome in post-menopausal women was found, verifying that the physiotherapy treatment is beneficial in the post-menopausal women undergone Dynamic Hip Screw with plating for Intertrochanteric fractures.